2019
DOI: 10.1007/s40271-019-00391-w
|View full text |Cite
|
Sign up to set email alerts
|

A Picture is Worth a Thousand Words: The Role of Survey Training Materials in Stated-Preference Studies

Abstract: Background Online survey-based methods are increasingly used to elicit preferences for healthcare. This digitization creates an opportunity for interactive survey elements, potentially improving respondents' understanding and/or engagement. Objective Our objective was to understand whether, and how, training materials in a survey influenced stated preferences. Methods An online discrete-choice experiment (DCE) was designed to elicit public preferences for a new targeted approach to prescribing biologics ("biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 55 publications
0
31
1
Order By: Relevance
“…Comprehension of the survey by participants will be ensured through use of the educational tool that was designed. Vass et al ( 86 ) showed in their study that the use of an animated educational tool did not change preferences of respondents, but improved choice consistency. The information presented in the educational tool developed in the current research covers information needs of patients and was validated by hematologists and piloted with patients.…”
Section: Discussionmentioning
confidence: 98%
“…Comprehension of the survey by participants will be ensured through use of the educational tool that was designed. Vass et al ( 86 ) showed in their study that the use of an animated educational tool did not change preferences of respondents, but improved choice consistency. The information presented in the educational tool developed in the current research covers information needs of patients and was validated by hematologists and piloted with patients.…”
Section: Discussionmentioning
confidence: 98%
“…31 Educational tools have also been found to play a crucial role in measuring consumer preferences for new products. 32,33 A significant effect of residence (mainly Flanders vs. Wallonia) on all benefit thresholds was observed. A correlation was observed between residence and prior discussion on gene therapy with a clinician as proportionally more PWH in Wallonia had discussed gene therapy with their clinician.…”
Section: Sources Of Preference Heterogeneitymentioning
confidence: 96%
“…The DCE survey went through an extensive piloting process (pilot survey with 82 patients; consultation with two academic dermatologists) that was run in parallel with a similar survey designed for people with RA 15 . Changes were made to the levels and their associated images for ‘cost saving to the National Health Service (NHS)’ based on the results from the quantitative pilot.…”
Section: Methodsmentioning
confidence: 99%
“…An iterative process, conducted alongside developing a similar survey for people with RA, identified the relevant attributes. 15 The results from interviews conducted as part of a qualitative study in RA 16 and five focus groups (attended by a total of 51 individuals with RA) were supplemented with a psoriasis support group meeting (seven individuals), literature review of psoriasis and DCEs, and two clinical expert interviews to inform the selection of attributes and to ensure that participants understood the survey. The psoriasis support group meeting involved collating views of the online survey by presenting and discussing the training materials and the framing of the attributes and levels.…”
Section: Designing the Discrete Choice Experimentsmentioning
confidence: 99%